PENGEMBANGAN E-LKPD MATERI BILANGAN PECAHAN BERBASIS PROBLEM BASED LEARNING PADA KELAS IV SEKOLAH DASAR - Yunita Triwiyanti Pribadi; Dudung Amir Sholeh; Yetty Auliaty (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
Student worksheet usually in printed form, while Electronic student worksheet in digital form, so it could be accessed anywhere using the internet network. This study aims to develop and determine suitability of Electronic worksheets on fractional number material in grade 4th. Type of research is R&D using the 4-D Thiagarajan and Sammel model which consists of four step, 1) Define, 2) Design, 3) Develop, 4) Disseminate. The subjects of this research were 4th grade students of SDN Menteng Atas 01 Pagi. Data instruments in the form of observations, interviews, expert review and student response questionnaires. The expert review process is carried out on material, media, and language experts. The average result of the three experts is 86.20% and can be interpreted as "very feasible". The COVID-19 virus pandemic has made the field trial process only using the zoom application, namely with one to one evaluation and small group. The results of each field trial are 83.66% and 88.54%, which means "very feasible". Based on the test result of GEBEKA Electronic student worksheet, it is appropriate to use it as for learning fractional number material in grade 4th Elementary School.